A dual-layer cell-laden tubular scaffold for bile duct regeneration. (15th December 2021) - Yan, Jianing; Liu, Xixia; Liu, Jingyi; Zhang, Xinjie; Zheng, Qiang; Nan, Junjie; Lin, Mengjia; Pan, Haoqi; Wang, Yifan; Cai, Xiujun; Yin, Jun
Graphical abstract: Highlights: Dual-layer biliary scaffolds were prepared by a two-stage molding method. The inner layer is strong and the outer layer is suitable for cell growth. Cholic acid could induce MSCs embedded in hydrogels to cholangiocyte-like cells. Dual-layer induced-cell-laden scaffolds could promote biliary regeneration in vivo. Abstract: Bile duct injury is a common complication of hepatobiliary surgeries in clinical practice with poorly satisfactory treatment outcomes. Implanting a tissue-engineered tubular scaffold for supporting and replacing defected native bile duct is an important treatment option for bile duct injury. Here a dual-layer tubular scaffold with poly (lactic-co-glycolic acid) (PLGA) inner layer and gelatin methacrylate (GelMA)/poly (ethylene glycol) diacrylate (PEGDA) outer layer was fabricated using a two-stage molding method for bile duct regeneration. Further, induced mesenchymal stem cells (MSC)-derived cholangiocyte-like cells were embedded in the outer layer during fabrication. The inner layer of PLGA offered adequate mechanical strength for the scaffold, and the outer layer of GelMA/PEGDA provided excellent biocompatibility and conditions for the MSCs and their induced differentiation. Moreover, cholic acid and its derivates are believed to induce MSC-cholangiocyte differentiation in two-dimensional culture and could affect the MSCs transforming to cholangiocyte-like cells in the hydrogel. Induced-MSC-laden GelMA/PEGDA-PLGA dual-layer tubular scaffold and PLGA single-layer scaffold were transplanted into animal models for assessing the repair effect on bile duct injury. After 12 wk, induced-MSC-laden dual-layer tubular scaffold promoted bile duct repairing and enhanced more intact biliary epithelium regenerating compared to PLGA single-layer scaffold. Therefore, the induced-MSC-laden dual-layer tubular scaffold with superior biocompatibility and distinct function of inducing differentiation exerted a satisfactory effect on bile duct regeneration and could provide an ideal option for the clinical treatment of bile duct injury in the future.